2016
DOI: 10.3847/0004-637x/830/1/19
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic-Ray Small-Scale Anisotropies and Local Turbulent Magnetic Fields

Abstract: Cosmic-ray anisotropy has been observed in a wide energy range and at different angular scales by a variety of experiments over the past decade. However, no comprehensive or satisfactory explanation has been put forth to date. The arrival distribution of cosmicrays at Earth is the convolution of the distribution of their sources and of the effects of geometry and properties of the magnetic field through which particles propagate. It is generally believed that the anisotropy topology at the largest angular sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 83 publications
1
41
0
Order By: Relevance
“…Giacinti & Sigl (2012) also showed that these local magnetic field structures could create such anisotropies. Similar work to our code was calculated in López-Barquero et al (2015). However, that study primarily looked at particles with PeV-scale energies, where the Larmor radius and mean-free-path are on parsec scales, similar in size to the coherence length of the magnetic turbulence.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Giacinti & Sigl (2012) also showed that these local magnetic field structures could create such anisotropies. Similar work to our code was calculated in López-Barquero et al (2015). However, that study primarily looked at particles with PeV-scale energies, where the Larmor radius and mean-free-path are on parsec scales, similar in size to the coherence length of the magnetic turbulence.…”
Section: Discussionmentioning
confidence: 88%
“…Full MC integration of these TeV particles is intractably slow, so this was why a hybrid diffusion+MC method was needed. Additionally, López-Barquero et al (2015) assumed that the source population was diffuse, which allowed them to time-reverse incoming particles to get maps of the anisotropic sky. However, our code allows for general source distributions in which particular CR sources are dominating the anisotropy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of l min can be large in partially ionized gas (see Xu et al 2015). Due to the differences of r L for protons and electrons Eq.…”
Section: Damping By Subalfvenic Strong Turbulencementioning
confidence: 99%
“…In principle, this could be due to a coincidental alignment of the CR density gradient and the field direction, but we interpret it as supporting the view that CRs diffuse mainly along field lines, rather than across them, in which case the density gradient is not strongly constrained. Although explanations have been advanced for small-scale anisotropies that can arise from the configuration of the interstellar magnetic field (Giacinti & Sigl 2012;Battaner et al 2015;López-Barquero et al 2016), both the amplitude and the shape of the global anisotropy remain unexplained. Until now, the amplitude has attracted most of the attention (Blasi & Amato 2012;Pohl & Eichler 2013;Kumar & Eichler 2014;Mertsch & Funk 2015).…”
Section: Introductionmentioning
confidence: 99%